Morphological types and seasonal variation in eggs of zooplankton species from bottom sediments in Bahia Blanca Estuary, Argentina - Diodato, Soledad Lorena; Berasategui, Anabela Anhi; Hoffmeyer, Monica Susana (Brazilian Journal of Oceanography)
Resting egg production is a survival mechanism in zooplankton species against adverse environmental conditions. Egg accumulation in the upper layer of the bottom sediments is fundamental to the resurgence of the populations of these species when conditions become more favourable. Rotifers, such as Synchaeta sp. and planktonic copepods such as Acartia tonsa and Eurytemora americana are commonly found in Bahía Blanca Estuary and they produce resting eggs. We studied eggs isolated from samples of bottom sediments obtained from two sites located within the inner part of Bahía Blanca Estuary (Cuatreros Port and Ing. White Port). The aims of our work were to describe the morphological types of eggs found in bottom sediments; to try to identify to which species they belong; to corroborate the identity of some of them by means of incubations; and to determine either the spatial or seasonal presence of morphological types according to the sampling site. Sediment samples were collected from Cuatreros Port on a monthly basis from January to December 2003 and samples from Ing. White Port were collected from the area close to the industrial zone only in April 2004. All samples were treated following the sugar flotation method of Onbé. The eggs were observed under stereomicroscope and light microscope. Besides, incubation experiments with eggs were sometimes carried out. Five morphological types of eggs (type A, B, C, D and E) were found in the sediments from Cuatreros Port whereas three types of eggs were found at Ing. White Port (F, G and H). Of the 8 morphological types of eggs found in this study, only those of the rotifer Synchaeta sp. in Cuatreros Port and the copepod A. tonsa in the two sampling sites were confirmed to be respectively diapausal and “delayed -hatching”. As regards the seasonal variation of the eggs found in the sediments from Cuatreros Port and the active forms of the populations of Synchaeta sp. and A. tonsa, our study confirms the presence of eggs in the sediment either in periods of time during which ...